Raj'i Talaq Law According to the Shafi'i School in Polyandry Cases (Case Study of Banda Aceh Shar'iyah Court Decision Number 383/Pdt.G/2020/MS. Bna) - Fahmi, Mutiara; Iqbal, Muhammad; Akbar, Rizki; Nurdin, Abidin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Islamic law and Indonesian legislation basically emphasize that marriage can only have one partner. In the Shafi'i school, Ash-Sharbini al-Khatib says,